Economic Valuation of Ringgung Coast, Lampung Province: Does Small Area of Coast should be Abandoned? - Widiastuti, Endang L; Lestari, Pamuji; Dasaluti, Teli (Journal of Indonesian Coral Reefs, 2012)
The study in the Southeast Asia regarding fisheries, tourism, including aesthetic value estimated the sustainable economic benefits per kmÃÂ² of healthy coral reef ranging from US$23,100 to 270,000. The question is how this goes for limited area consisted of mangrove-sea grass-coral reef, which found in many coasts throughout Indonesia archipelago. Should it be ignored? The purpose of the study was to indicate the existing economic values of limited coastal area consisted of mangrove, sea grass be, and coral reefs of the Ringgung coast of Pesawaran, Lampung Province. The results indicated that from coast length of 2.4 km, the total area of the wetland is approximately 78 ha consisted of 4.75 ha of mangrove, 22 ha of sea grass bed, and more than 50 ha of coral reefs. The economics values of the area study were predominantly used for grouper farms, with more than 15 individual farms, recreation, and Rizhopora culture (for seedlings) operated by locals. The economic values of the Ringgung coast by using direct use value of the grouper farms indicated that the yearly fish productivity was grossly of US$ 640,985. This number could be added up by the other economic values, such as recreation and saling of Rizhopora seedling. We can conclude that this economic values provided by the coastal ecosystem should be made to conserve the existing ecosystem. Besides, in order to maintain sustainable economic of the ecosystem, some consideration should be made in regard of carrying capacity for grouper farms in the area study.